Emotional intelligence of university men and women in Juliaca city - Rodriguez Calle, Martha Elizabet (2022)
Objective: To determine the significant relationship between dependence on social networks andacademic procrastination in university students of the I and II semester of a university in Juliaca.Methodology: Non-experimental design, cross-sectional and correlational type, the study samplewas 122 male and female students, who were administered the instruments: Scale of Dependenceon Social Networks (2013) and Scale of Academic Procrastination, which presented reliability ofuse. Result: There is a significant correlation between dependency on social networks (DRS) andacademic procrastination (Rho=0.465; p=0.0001), as well as for the dimensions of DRS, dependency(Rho=0.449; p=0.0001), tolerance (Rho=0.417; p=0.0001) and withdrawal (Rho=0.489; p=0.0001).Conclusion: The greater dependence on social networks, a higher level of academic procrastinationis expected in university students